James Monroe-Encyclopedia of Presidents - Fitz-Gerald, Christine Maloney (Chicago, IL: Childrens Press, 1986)
Summary: The life and long political career of the fifth president of the United States whos Monroe Doctrine proclaimed opposition to further European control in the Western hemisphere.
Keywords: Monroe,James--1758-1831.; Presidents